Therapeutic Management of Anaplasmosis in a Kid - Archanna; H, Prabhavathy; Premalatha N; Senthilkumar K; Kavitha S; Vijayakumar G (Indian Journal of Veterinary Medicine, 2025)
A non-descript male kid about 4 months old was presented with complaint of anorexia, lethargic and tick infestation. Clinical examination revealed elevated temperature (104.6⸰F), pale conjunctival mucous membrane, anaemia and enlarged lymph nodes. Peripheral blood smear showed the presence of Anaplasma organism in the RBCs. Whole blood was collected and subjected to PCR, in which sample shown positive for Anaplasma ovis infection. The kid was administered with oxytetracycline @ 20 mg/kg body weight I/M, Sharkoferrol vet (@ 5 gm daily) and B- complex injection (@ 1 mL I/M) at an interval of 48h. Significant clinical improvement was noticed after five days of treatment.